Socioeconomic problems of housing in the regions of Arequipa and Piura, 2004 - 2017 - Aranda Dioses, Edith (2019)
In the present study, we will analyze the socioeconomic characteristics of households in relation to the dwellings they occupy in the regions of Arequipa and Piura, based on information from the National Household Survey (ENAHO, INEI, 2004-2017). We have selected these departments because, due to their population concentration and socioeconomic dynamics, they are representative of the housing problem in the country. We also consider that the housing policy through the MiVivienda and Techo Propio programs has had an important development in the regions in the last years, in general the beneficiaries of this last program, oriented to the social sectors C and D, are concentrated in provinces (Ministry of Housing, Construction and Sanitation (MVCS), 2015). From this frame of reference we will address the housing situation in the Arequipa and Piura regions, especially its impact on the quality of life of the inhabitants, and we will approach some of its implications in order to promote appropriate housing policies for achieve inclusive and sustainable cities (MVCS-UNIPRAVI, 2011). The aim is to answer the following question: How do the socioeconomic characteristics of households influence the quality of housing? We will evaluate if the homes reach minimum parameters of habitability that provide favorable conditions to meet the needs of families. That is, we are interested in addressing the qualitative deficit of housing in the regions mentioned.